Membangun Mental Positif Selama Masa Pandemi Covid-19 Melalui Pengusaan Teknologi Sederhana di Panti Karya HEPHATA HKBP (Jurnal Suluah Komunitas, 2021)
The conditions of the Covid 19 pandemic are experienced by various levels of society, the impact is huge in various sectors. Not only the health sector but also the economy, education, entrepreneurship, and employment. In the world of education, the COVID-19 pandemic has a huge impact, especially on children with special needs and disabilities. Their limited condition needs to be developed to be able to survive even the most difficult conditions. Meanwhile, during the pandemic, a quarantine was imposed to break the chain of Covid 19, all people had to carry out work, worship, and study activities from home. During the quarantine process, they were confused about carrying out activities, so they often came into conflict with themselves and with people outside of themselves so that a positive mentality must be built to be able to motivate children with special needs and disabilities. The method used in this PKM is the method of community education and training in the form of Focus Group Discussions (FGD) for orphanage teachers, orphanage administrators, residents around the orphanage environment, and observers with special needs. PKM was carried out at the HKPB Hepatha Work Home, Sintong Marnipi Village, Laguboti, Toba Regency, North Sumatra. Through PKM activities, it is hoped that seminar participants can continue to help children with special needs and disabilities to be able to carry out positive activities and think positively while going through the COVID-19 pandemic.